Ajātaśatru among the Pudgalavādins: A Leaf of the Saṃmitīya Śāmaṇṇaphala-mahāsūtra in Bhaikṣukī Script - Tournier, Vincent (Indo-Iranian journal, 2024)
This article presents a close and contextualised study of a newly available folio belonging to a larger manuscript written in Bhaikṣukī script and preserved in the Tibetan Autonomous Region of China. A total of 78 folios of a larger bundle survive, transmitting at least ten sūtras—consistently called mahāsūtras—in a Middle Indo-Aryan variety that is distinctive of Saṃmitīya canonical transmission. Most of these extant sūtras are paralleled in the “Division on the aggregate of morality” (P. Sīlakkhandha-vagga, Skt. Śīlaskandha-nipāta) of all three other extant Collections of Long Discourses (P. Dīgha-nikāya, Skt. Dīrghāgama). Evidence thus suggests that the bundle in question preserves the beginning of a complete Saṃmitīya *Drīghāgama. The illuminated leaf edited and studied here transmits the final part of the eighth discourse of the collection, likely titled *Śāmaṇṇaphala-mahāsūtra. This final section preserves a new version of the episode recounting King Ajātaśatru’s repentance and conversion at the end of the Buddha’s discourse. The introduction to this article situates this newly available fragment in relation to a growing body of evidence on the Dīrghāgama and the broader canonical transmission of the Saṃmitīyas, before discussing the specificity of the Ajātaśatru episode vis-à-vis other early accounts of the same episode. The core of this article is the second part, which provides a rationale for the edition of this fragment and the reconstruction of its lacunae. It then presents a diplomatic edition of the folio, followed by a restored, curated text. In the latter, the Saṃmitīya sūtra is presented with detailed lexicographic notes, a translation, and with the synoptic text of the three closest parallels from the Pāli Dīgha-nikāya, the Chinese *Dīrghāgama, and the Sanskrit Dīrghāgama. In particular, the Sanskrit parallel as transmitted in the codex unicus of the Dīrghāgama is here critically edited for the first time, also collating anew the relevant portion of the manuscript of the extant Sanskrit Saṅghabhedavastu of the Mūlasarvāstivādins.